Rate of Convergence of Modified Baskakov-Durrmeyer Type Operators for Functions of Bounded Variation. (1st July 2014) - Patel, Prashantkumar; Mishra, Vishnu Narayan
Abstract : We study a certain integral modification of well-known Baskakov operators with weight function of beta basis function. We establish rate of convergence for these operators for functions having derivative of bounded variation. Also, we discuss Stancu type generalization of these operators.